The Affordable Care Act and the COVID-19 pandemic: A regression discontinuity analysis - Rajashri Chakrabarti; Lindsay Meyerson; William Nober; Maxim Pinkovskiy (Federal Reserve Bank of New York, 2020)
Did Medicaid expansion under the Affordable Care Act affect the course of the COVID-19 pandemic? We answer this question using a regression discontinuity design for counties near the borders of states that expanded Medicaid with states that did not. Relevant covariates change continuously across the Medicaid expansion frontier. We find that 1) health insurance changes discontinuously at the frontier, 2) COVID-19 cases do not change discontinuously at the frontier but the precision of this estimate is low, 3) COVID-19 deaths do not change discontinuously at the frontier and the confidence intervals exclude large declines in deaths in Medicaid expansion areas, 4) smart thermometer readings of fever rates from Kinsa, Inc. do not change discontinuously at the frontier, and 5) COVID-19-related doctor visits discontinuously increase in Medicaid expansion areas.
Keywords: C21; I13; I18; 330; Affordable Care Act; COVID-19; Medicaid; regression discontinuity